Defect Enrichment in Near Inverse Spinel Configuration to Enhance the Persistent Luminescence of Fe3+. Issue 1 (31st October 2021) - Zhou, Zhihao; Zhang, Shuai; Le, Yakun; Ming, Hong; Li, Yang; Ye, Shi; Peng, Mingying; Qiu, Jianrong; Dong, Guoping
Abstract: Spinel configuration is a kind of broadly considered host candidate when designing persistent luminescence (PersL) materials due to the easy generation of vacancies and anti‐site defects. Here, a new strategy of defect enrichment for the activation of PersL is proposed, and in contrast to the spinel configuration, it is demonstrated that the crystal structure of near inverse spinel ensures more numerous defects to activate the near‐infrared (NIR) PersL of Fe 3+ . Fe 3+ ‐doped MgGa2 O4 displays the PersL band in the range of 600 to 900 nm and possesses a super‐long PersL duration time >15 h. The optical analysis and the calculation of density functional theory unravel that the near inverse spinel structure can lower the carrier transfer barriers to accelerate the formation of carrier trap states within the bandgap. Therefore, more numerous defects in this structure may participate in the trapping and de‐trapping process by comparison with the normal spinel configuration. These findings are expected to accelerate the development of new PersL materials through Fe 3+ doping toward versatile biological applications in NIR window. Abstract : A new strategy of defect enrichment for the activation of persistent luminescence (PersL) is proposed. It is unraveled that near inverse spinel structure can lower the carrier transfer barriers to accelerate the formation of carrier trap states within the bandgap. Therefore, the crystal structure of near inverse spinel ensures more numerous defects to activate the near‐infrared PersL of Fe 3+ .